Recent Advances in Nanotechnology for the Prevention and Management of OSCC - Misra, Swagatika; Meghwanshi, Madhuri; Sharma, Ankit; Alam, Meraj; Parveen, Shama; Kumar, Vijay; Singh, Manju (Journal of Neonatal Surgery, 2025)
Oral Squamous Cell Carcinoma (OSCC) is among the most common malignancies globally, contributing substantially to oral cancer-related morbidity and mortality. Traditional treatment methods, including surgery, radiation therapy, and chemotherapy, exhibit limitations such as non-specific medication distribution, systemic toxicity, and recurrence. Recent breakthroughs in nanotechnology and drug delivery technologies have resulted in the development of theranostic techniques, which provide both therapeutic and diagnostic functions within a single platform. Novel drug delivery systems (NDDS) facilitate targeted drug administration, augment bioavailability, and reduce adverse effects, ultimately enhancing patient outcomes. The shift from traditional treatment to theranostic intervention utilises nanoparticles, liposomes, dendrimers, and micelles to encapsulate anticancer drugs, facilitating controlled and localised medication release. Moreover, intelligent nanocarriers that include imaging agents provide real-time observation of drug distribution and tumour response, allowing for personalised treatment approaches. Diverse nanoplatforms, including gold nanoparticles, quantum dots, and mesoporous silica nanoparticles, have been thoroughly investigated for their multifunctionality in the therapy of OSCC. Moreover, biomimetic and stimuli-responsive drug delivery systems boost therapeutic efficacy while minimising systemic toxicity. This study underscores the transition from conventional OSCC treatments to nanomedicine-based theranostic strategies, highlighting their potential to transform oral cancer therapy. Notwithstanding significant progress, obstacles including large-scale manufacturing, regulatory approvals, and clinical implementation must be resolved for general acceptance. Future research should concentrate on enhancing nanoplatforms to attain precision oncology, hence improving prognostic and therapeutic results for OSCC patients. The amalgamation of NDDS with artificial intelligence and personalised medicine may further transform OSCC treatment, establishing theranostics as a fundamental element in oral cancer management